Predictability of the vault after posterior chamber phakic intraocular lens implantation using anterior segment optical coherence tomography. Issue 8 (August 2019) - Igarashi, Akihito; Shimizu, Kimiya; Kato, Sayaka; Kamiya, Kazutaka
Abstract : Purpose : To determine whether vault measurements after placement of a hole implantable collamer lens (hole ICL) (KS‐AquaPORT) can be predicted by angle‐to‐angle (ATA) and white‐to‐white (WTW) measurements obtained with anterior segment optical coherence tomography (AS‐OCT). Setting : Sanno Hospital, Tokyo, Japan. Design : Retrospective case series. Methods : Eyes were observed for 3 months after hole ICL implantation for myopia or myopic astigmatism. Central vault, ATA, and WTW measurements were obtained before and after surgery using the swept‐source AS‐OCT CASIA2 system. Results : The study included 44 eyes (23 patients). The mean patient age and preoperative spherical equivalent, ATA, and WTW values were 36.2 years ± 8.8 (SD), −6.23 ± 3.41 diopters (D), 12.03 ± 0.40 mm, and 11.72 ± 0.40 mm, respectively. The safety index and efficacy index 3 months postoperatively were 1.13 ± 0.21 and 0.91 ± 0.30, respectively. Regarding predictability, 93.2% of eyes were within ±0.50 D of the attempted correction and all eyes were within ±1.00 D. The reproducibility coefficients for the ATA distance and WTW distance were 0.998 and 0.960, respectively. The mean postoperative central vault was 491.6 ± 189.5 μm. There was a significant correlation between postoperative vault and the ICL size and ATA distance (Spearman rank correlation coefficient r = 0.59, P < .001) but not between the ICL size and WTW distance ( r = 0.27, P = .08). Conclusion : The ATA measurements had higher reproducibility than the WTW measurements on AS‐OCT, making it is a more important predictor of postoperative vault.